Miniso Royal Plaza Surabaya Consumer Impulse Buying Behavior - Nurul Silfiyah Isnaini; Noerchoidah (Universitas Dinamika, 2021)
This research is to analyze the effect of price discount, visual merchandising, shopping lifestyle on impulse buying of Miniso Royal Plaza Surabaya consumers. The research data used were 105 respondents using multiple linear regression to analyze the data. The empirical results of the study prove that price discount has a positive and significant effect on impulse buying, visual merchandising has a positive and significant effect on impulse buying, shopping lifestyle has a positive and significant effect on impulse buying. Furthermore, it was simultaneously found that price discount, visual merchandising, shopping lifestyle onimpulse buying.